PORTARIA PRPB Nº 116, DE 08 de JUNHO DE 2021. - Sergio Rodrigo Pimentel de Castro Pinto (DMPFe, Administrativo de 10/06/2021, p. 13., 2021)
Dispensa e designa Chefe Substituto do Setor Administrativo da PRM-Sousa/PB.